Regeneration of Sn4+ from Sn2+ solution during electrowinning process using anion exchange membrane. Issue 1 (2nd January 2019) - Jung, Moonchul; Yoo, Kyoungkeun; Alorro, Richard Diaz
ABSTRACT: Electrowinning process to regenerate Sn 4+ from Sn 2+ in HCl solution using an electrowinning cell with anion exchange membrane was proposed to suggest a novel recycling process to recover Sn. During the tests, the effects of initial Sn 2+ concentration on the regeneration of Sn 4+ were investigated under the following condition; 7, 000 mg/L, 10, 000 mg/L, and 13, 000 mg/L of Sn 2+, 1 M HCl, 250 A/m 2 of current density, graphite anode, titanium cathode, room temperature, and 2 h. Electro-deposited Sn on the cathode showed dendritic structure regardless of the Sn 2+ concentration and no change of Sn concentration was observed in the anolyte. Leaching tests were performed using the anolyte, obtained from the electrowinning tests, to examine the amount of regenerated Sn 4+ concentration during electrowinning process. Based on the results of Sn leaching tests, it was found that 84.44%, 81.03%, and 79.43% of Sn 4+ were regenerated from 7, 000 mg/L, 10, 000 mg/L, 13, 000 mg/L initial concentration of Sn 2+ solution, respectively. Consequently, it was found that the regeneration of Sn 4+ can occur during the electrowinning process at the same time with Sn recovery and Sn 4+ can be reused as an oxidant to leach Sn successfully.